The Importance of Culture Change Associated With Novel Surgical Approaches and Innovation: Does Perioperative Care Transcend Technical Considerations for Pulmonary Lobectomy? - Freystaetter, Kathrin; Waterhouse, Benjamin R.; Chilvers, Nicholas; Trevis, Jason; Ferguson, Jonathan; Paul, Ian; Dunning, Joel (Frontiers in Surgery, 2021)
Robotic thoracic surgery for pulmonary lobectomy was introduced at our unit in 2015, along with enhanced perioperative patient care pathways. We evaluated the effect of this practice change on short-term outcomes. Data on all adult patients who underwent a lobectomy in our unit between 2015 and 2019 were obtained retrospectively from our surgical database. Patients fell into three groups: conventional open surgery via thoracotomy, video-assisted thoracoscopic surgery (VATS), and robot-assisted thoracoscopic surgery (RATS). Survival was defined as survival to discharge. Our cohort included 722 patients. 392 patients (54.3%) underwent an open operation, 259 patients (35.9%) underwent VATS surgery, and 71 patients (9.8%) underwent a robotic procedure. Comparing these surgical approaches, there was no statistically significant difference in the overall incidence of post-operative complications (p=0.15) as well as the incidence of wound infections, arrhythmias, prolonged air leaks, respiratory failure, or ICU readmissions. Additionally, there was no statistically significant difference in survival to discharge (p=0.66). However, patients who had a VATS procedure were less likely to develop a post-operative chest infection (p=0.01). Evaluating our practice over time, we found a decrease in the overall incidence of postoperative complications (p=0.01) with an improvement in survival to discharge (p=0.02). In our experience, VATS lobectomy was associated with a lower incidence of post-operative chest infections. However, the limitations of our study must be considered; factors such as patient selection that may have had a substantial impact. The culture change associated with adoption of a VATS and robotic surgical programme appears to have corresponded with an improved survival to discharge for all lobectomy patients, irrespective of surgical approach. Perioperative care may therefore have a more significant impact on outcomes than technical considerations.